Sastra Dan Bahasa Sebagai Sarana Mencerdaskan Generasi Muda Dalam Memahami Keberagaman Budaya - Wala Azizah; Agustin Riyanti; Mujino Mujino; Ruwaida (Cordova Journal, 2025)
ABSTRACT Background of the Research: The cultural diversity in Indonesia is one of the treasures that needs to be understood and appreciated by the younger generation. In this context, literature and language play an important role as tools to educate the youth in understanding and appreciating cultural differences. Purpose: This research aims to explore the role of literature and language as a means to educate the younger generation in understanding cultural diversity in Indonesia. Methodologies: This study employs a qualitative approach with subjects consisting of students and teachers from several schools. Data were collected through in-depth interviews, focus group discussions, and direct classroom observations. Data analysis was conducted using thematic analysis. Principal Results: The findings indicate that the teaching of literature and language significantly enhances students' understanding of cultural diversity, as well as develops character, empathy, and tolerance among the youth. The use of local literary works and regional languages has proven to strengthen students' cultural identity. Major Conclusions: The study concludes that literature and language are effective tools in building cultural awareness and reinforcing national identity amidst existing diversity .Contributions to the Field: This research provides significant contributions to the development of educational curricula in Indonesia and serves as a reference for educators and policymakers in formulating better teaching strategies. Keywords: Literature, Language, Cultural Diversity, Education, Youth